2016
DOI: 10.1002/jemt.22677
|View full text |Cite
|
Sign up to set email alerts
|

Comparative B‐mode and Doppler renal ultrasonography with histopathological findings in dogs positive for canine visceral leishmaniasis

Abstract: Morphological parameters and renal flow were assessed and measured in six clinically healthy dogs with negative serological and parasitological examinations for canine visceral leishmaniasis (CVL) and six dogs with CVL-positive serological and parasitological tests and asymptomatic condition of the disease. Kidney length and diameter were measured and compared with the aorta/kidney ratio. Alterations in flow were measured using the flow velocity (cm/s) and resistance index (RI). Renal function was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
1
0
3
Order By: Relevance
“…A positive correlation between creatinine levels and RI and PI was reported in a study on patients with CRF in human medicine (Peterson et al, 1997). In addition, Baltazar et al (2016) and Torroja (2007), found a positive correlation between these parameters in cats and dogs. In the study of dogs managed in 1996, renal diseases were compared with the RI value and it was reported that there was no correlation between RI value and urea and creatinine (Morrow et al, 1996).…”
Section: Resultsmentioning
confidence: 75%
“…A positive correlation between creatinine levels and RI and PI was reported in a study on patients with CRF in human medicine (Peterson et al, 1997). In addition, Baltazar et al (2016) and Torroja (2007), found a positive correlation between these parameters in cats and dogs. In the study of dogs managed in 1996, renal diseases were compared with the RI value and it was reported that there was no correlation between RI value and urea and creatinine (Morrow et al, 1996).…”
Section: Resultsmentioning
confidence: 75%
“…Права нирка лежить на рівні другого та четвертого хребця, а ліва -на рівні четвертого-п'ятого, іноді досягаючи шостого поперекового хребця. В інших літературних джерелах топографія нирки у собак має вікові та індивідуальні особливості (Baltazar et al, 2016;DEPalma et al, 2019). У нормі кожна нирка у собаки має лише єдину ниркову артерію, що відходить від черевної аорти (Sajjarengpong & Adirektaworn, 2006).…”
Section: результати та їх обговоренняunclassified
“…Além disso, a perfusão dinâmica e informações sobre a resistência vascular são úteis para monitorar a evolução de pacientes com doença renal crônica, proporcionando uma nova abordagem para a análise na prática clínica (BALTASAR et al, 2016).…”
Section: Introductionunclassified